Peran Supervisi Kepala Sekolah dalam Mengembangkan Profesionalitas Guru Madrasah - Rosyidatul Mu'ammaroh, Nurul Lail (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
The supervision essentially contains several main activities, namely the continuous coaching, professional ability development of personnel, improvement of teaching and learning situation with the final target achievement of educational goals and personal growth of students. Supervision done by headmaster as supervisor is to help teachers improve teaching situations in a broad sense. One of the tasks in order to improve the quality of teaching in schools is to develop and analyze the curriculum applied in school. In order to analyze the school curriculum, the principal task is to help teachers improve the teaching profession.